Auditory Discrimination Training in Articulation Therapy - A Pilot Study - Geetha YV; Subrahmanyaiah MG; Rathna N (Journal of All India Institute of Speech and Hearing, 1970)
It has long been believed that articulation errors are the result of faulty discrimination and that discrimination training is  a pre-requisite for the  correct production of the desired sound. Auditory training has been considered as the first step in the correction of defective sounds  Van Riper and Irwin (1958), Van Riper (1939), Berry and Eisenson (1956), Kronval et al, (1954). However this  stand  is not universal. Winitz (1969) suggests that while phonemic distinction can be learned before articulatory productions, articulatory experience will affect later  discrimination. He concludes that sound discrimination learning is necessary but not a sufficient condition for sound learning (Winitz 1965). Contrary to this Ladefoged (1967), Backus and Beasley (1951) and Kumudavalli (1973) have questioned the importance of discrimination training in the learning of  articulation.